Progress in Electrolyte-Free Fuel Cells - Lu, Yuzheng; Zhu, Bin; Cai, Yixiao; Kim, Jung-Sik; Wang, Baoyuan; Wang, Jun; Zhang, Yaoming; Li, Junjiao (Frontiers in Energy Research, 2016)
Solid Oxide Fuel Cell (SOFC) represents a clean electrochemical energy conversion technology with characteristics of high conversion efficiency and low emissions. It is one of the most important new energy technologies in the future. However, the manufacture of SOFCs based on the structure of anode/electrolyte/cathode is complicated and time-consuming. Thus, the cost for the entire fabrication and technology is too high to be affordable and challenges still hinder commercialization. Recently, a novel type of Electrolyte -free fuel cell (EFFC) with single component was invented which could be the potential candidate for the next generation of advanced fuel cells. This paper briefly introduces the EFFC, working principle, performance and advantages with updated research progress. A number of key R&D issues about EFFCs have been addressed and future opportunities and challenges are discussed.